»Daraus kündten auch die Graeci lärnen« Die Bemühungen des Martin Crusius (1526-1607) um ein Luthertum der Griechen - Neuendorf, Paul Achim (Heidelberg University Publishing (heiUP), 2022)
In search of subsidies for the publishing of his Greek and Latin oeuvre, the Corona Anni, Professor Martin Crusius of Tübingen (1526-1607) pointed out in a letter to Johan Papius, court physician at Ansbach, that it might teach even the Greeks to preach the word of God truly. At this point in time, Crusius could look back on nearly thirty years in which he had exerted himself body and soul for the dissemination of the Lutheran teaching among the Greek-speaking Christians. His 'mission' had begun when his former student Stephan Gerlach had been chosen to travel from the university town in Württemberg to Constantinople as embassy preacher in 1573. Up until his death, Crusius pursued his project of establishing the essentials for a Greek Lutheranism and sending these - at times on adventurous paths - to their recipients.